Autosomal dominant multicentric infantile myofibromatosis: A case report - Jessica Justus Kurian; Megan R. Lyle (Elsevier, 2024)
Background: Infantile myofibromatosis (IM) is a rare disorder of benign fibrous tumors, where severity and prognosis depend on the location of tumors, particularly if visceral organs are affected. Most cases of IM are sporadic. However, some familial cases of multicentric IM have been reported, primarily involving genes PDGFRB and NOTCH3. Case report: We describe the clinical features and clinical course of two African American siblings with autosomal dominant multicentric IM caused by a novel mutation in the platelet-derived growth factor receptor β (PDGFRB) gene, c.1679C > T, resulting in p.Pro560Leu. This mutation was inherited from their mother, who was an asymptomatic carrier. Conclusion: The PDGFRB gene mutation, c.1679C > T, is a novel mutation that causes multicentric IM with an autosomal dominant inheritance pattern. It is difficult to determine whether chemotherapy regimens are effective or whether tumor development and recession proceed along their natural course despite medical intervention.